Turn Threats into “Treatments”? Social Bots’ Possible Applications in Health Communication during Pandemics - Zhenling Sun (Jurnal Audiens, 2021)
COVID-19 pandemic is a global Crisis, social media platforms have been a significant site of getting information and arouse discussions. However, social bots have risen on the online social networks, social bots are applications that existing in cyber space merely and they can mimic human users to interact with you following their own logic, there are the features of “Intangible”、“personate” and “automatic”. Evidence suggests that social bots did harm to the Health Communication during COVID-19 pandemic, researchers found that social bots contributed to diffuse political issues stir negative emotions, spread rumor. Social bots often have a negative association, but there are many bots which perform benign tasks. This study analysis the reasons bots performed badly in COVID-19 pandemic first, then discuss about how to turn the “threats” to “treatments”, proving that social bots can act as a positive role in different periods of Health Emergencies.